The influence of exercise adherence on peace of mind among Chinese college students: a moderated chain mediation model - Liu, Feiyang; Yu, Ping; Wu, Jinlong; Guo, Liya (Frontiers in Public Health, 2024)
Exercising adherence constitutes a pivotal approach for college students to maintain physical well-being, while peace of mind serves as a crucial indicator of their psychological health. However, few previous studies have delved into the relationship between these two variables. Our study endeavors to investigate the association between the exercise adherence and the peace of mind of college students.The Exercise Adherence Questionnaire, Meaning in Life Questionnaire, Brief Self-Control Scale, Peace of Mind Scale and Self Acceptance Questionnaire were tested on 1520 college students from four universities in western China, and SPSS 25.0 and Mplus 8.3 were used for analysis.The results indicate a significant positive correlation between exercise adherence and meaning in life (r=0.208, p<0.001), self-control (r=0.210, p<0.001), and peace of mind (r=0.237, p<0.001) among college students. Mediation analysis reveals that exercise adherence has a significant direct effect on peace of mind in college students, with an effect size of 0.087. Moreover, meaning in life and self-control independently mediate the relationship between exercise adherence and peace of mind, with mediation effect sizes of 0.046 and 0.052, respectively. Additionally, meaning in life and self-control collectively exhibit a chain mediation effect, with a mediation effect size of 0.032. At the same time, the interaction terms of meaning in life and self-acceptance had a significant predictive effect on self-control (b=0.090, p=0.002).This study reveals both the relationship and intrinsic mechanisms by which exercise adherence influences the peace of mind among college students. Exercise adherence demonstrates a direct positive impact on peace of mind. Additionally, the association between exercise adherence and peace of mind is influenced by the individual mediating effects of meaning in life and self-control, as well as the chain mediation effect of meaning in life and self-control.Moreover, self-acceptance plays a positive role in regulating the relationship between meaning in life and self-control in the chain mediated pathway. This suggests that we need to encourage college students to develop the habit of exercise adherence and to carry out public welfare activities to enhance their meaning in life, self-control and self-acceptance, which will effectively promote their mental health.